2016
DOI: 10.1590/0103-6440201600647
|View full text |Cite
|
Sign up to set email alerts
|

Bonding Effectiveness of Universal Adhesive to Intracoronal Bleached Dentin Treated with Sodium Ascorbate

Abstract: This study evaluated the effect of restorative protocol with sodium ascorbate on the shear bond strength (SBS) of a universal adhesive to intracoronal bleached dentin. One hundred-and-twenty bovine dentin fragments were randomly divided into 12 groups (n=10), according to the bleaching procedure (unbleached and bleached) and restorative protocol (no treatment, 10% sodium ascorbate -10SA, 35% sodium ascorbate -35SA and two-step etch-and-rinse -ER or one-step self-etch -SE Scotchbond universal adhesive approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Another demonstrated that the reaction between the HP and SA was fast, and 5 min was enough for the SA to eliminate the free radicals (Freire et al, ). Some studies have shown that a 35% SA solution for a shorter period of time can reverse the negative effects of bleaching on dentin bonding (Ismail et al, ; Trindade, Moura, Raucci, Messias, & Colucci, ). These data agree with the findings of this study, which demonstrated that the bond strength can be increased by the short‐time application of SA (2 or 10 min) to the dentin immediately after bleaching.…”
Section: Discussionmentioning
confidence: 99%
“…Another demonstrated that the reaction between the HP and SA was fast, and 5 min was enough for the SA to eliminate the free radicals (Freire et al, ). Some studies have shown that a 35% SA solution for a shorter period of time can reverse the negative effects of bleaching on dentin bonding (Ismail et al, ; Trindade, Moura, Raucci, Messias, & Colucci, ). These data agree with the findings of this study, which demonstrated that the bond strength can be increased by the short‐time application of SA (2 or 10 min) to the dentin immediately after bleaching.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, since bonding is compromised by bleaching, the adhesive interface might be inclined to the formation of microgaps and their undesirable consequences such as adhesive failure, microleakage, and, eventually, secondary caries. Previous authors have observed a decrease in dentin bond strength immediately after 35% HP intracoronal bleaching (Hansen et al, ; Trindade et al, ; Vieira et al, ). Moreover, lower concentrations of bleaching agents (16% carbamide peroxide) have also adversely affected enamel shear bond strength immediately or 30 days after bleaching (Uysal, Er, Sagsen, Ustdal, & Akdogan, ).…”
Section: Introductionmentioning
confidence: 89%
“…Although sodium perborate, 35% hydrogen peroxide, and 35% carbamide peroxide are effective as intracoronal bleaching agents (Kaneko, Inoue, Kawakami, & Sano, ), they are able to promote undesirable changes in the composition and mechanical behavior of dentin structure (Attin, Paqué, Ajam, & Lennon, ; Cavalli et al, ; Chng, Palamara, & Messer, ; Chng, Yap, Wattanapayungkul, & Sim, ; de Oliveira, Teixeira, Ferraz, & Teixeira, ; Timpawat, Nipattamanon, Kijsamanmith, & Messer, ), such as the decrease in dentin ultimate (Cavalli et al, ) and bond strengths (Hansen, Frick, & Walker, ; Piemjai & Surakompontorn, ; Trindade, Moura, Raucci, Messias, & Colucci, ; Vieira, Silva‐Sousa, Pessarello, Rached‐Junior, & Souza‐Gabriel, ). The decrease in the microhardness of enamel and dentin comprises mineral loss of dental hard tissues.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,6,7,8 The difficulty in achieving a stable hybrid layer with dentin tissue is related to the hydrophilic nature and organic structure of the sealer, 9,10 which can interfere with the sealer-dentin interaction. 11 In fact, incomplete infiltration of resinous monomers into collagen fibers within the hybrid layer favors hydrolysis and degradation of collagen by metalloproteinase (MMP), thus reducing the bonding longevity. 12 MMPs are calcium-and zinc-dependent endopeptidases trapped within the mineralized dentinal matrix during tooth development in an inactive form.…”
Section: Introductionmentioning
confidence: 99%